Language Disorders and an Islamic Perspective - Harahap, Muhammad Parwis Halim; Aziz Siregar, Fatahuddin; Rasyid, Arbanur; Angraini Lubis, Anita (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This article examines language disorders and how the Islamic perspective views them. It is extraordinary that Islam contains all fields of science, and especially linguistics in the focus of this article. Islam does not only focus on studying religious issues but concerns all elements of life, including science. Therefore, this article was written based on the extraordinary nature of Islam in regulating everything.Data processing techniques in research are, by observing, reviewing, recording and collecting relevant data that is in accordance with the object of study in this research. In the use of verbal communication, each of us is equipped with language skills, but these abilities are not always the same, some are normal and some are abnormal. Not only opinions about the relationship between language and thought are discussed by Psycholinguistics/Neurolinguistics experts, religious perspectives also analyze and participate in the study of language and thought. When viewed from a religious perspective, the study of language and thought which was then based on the revelation of the Qur'an led to different interpretations of the meaningful content with the insights of experts from each period. Keywords: Language Disorders, Neurolinguistics, Islamic Perspective